2022
DOI: 10.5194/soil-8-177-2022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of cover crop and reduced disturbance tillage on soil pore size distribution and soil water storage

Abstract: Abstract. We studied the long-term impact of contrasting tillage and cover cropping systems on soil structure and hydraulic properties. Complete water retention and conductivity curves for the top (0–5 cm) and subsurface (20–25 cm) soils were characterized and contrasted. Dynamic water storage and retention were evaluated using numerical simulations in HYDRUS-2D software. Compared with standard-till (ST) and no-cover-crop (NO) systems, soils under no-till (NT) and cover cropping (CC) systems showed improved so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…This disparity in size has the potential to alter the pore size distribution in coarse-textured soil, specifically shifting it towards smaller pore sizes with a broader size distribution 29 , 30 . In other words, adding ASi to coarse-textured soil shifts the pore size distribution toward fine-textured soil 31 . Consequently, this shift ensures a gradual drainage of pores in response to a drop in matric potential.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity in size has the potential to alter the pore size distribution in coarse-textured soil, specifically shifting it towards smaller pore sizes with a broader size distribution 29 , 30 . In other words, adding ASi to coarse-textured soil shifts the pore size distribution toward fine-textured soil 31 . Consequently, this shift ensures a gradual drainage of pores in response to a drop in matric potential.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term combination of NTCC altered soil structure, as well as the soil hydraulic properties and water storage, compared to STCC. Our previously published determinations of soil hydraulic properties over time -as opposed to static analysis such as Araya et al (2022) -indicated that reduced disturbance with cover cropping led to a bimodal pore size distribution in surface soils (0-2 inch) (0-5 cm) and a 20% increase in water storage. Increased aeration and higher saturated hydraulic conductivity allow more water to be retained in the root zone without becoming waterlogged (Araya et al 2022).…”
Section: Soil Structure and Biologymentioning
confidence: 99%
“…Our previously published determinations of soil hydraulic properties over time -as opposed to static analysis such as Araya et al (2022) -indicated that reduced disturbance with cover cropping led to a bimodal pore size distribution in surface soils (0-2 inch) (0-5 cm) and a 20% increase in water storage. Increased aeration and higher saturated hydraulic conductivity allow more water to be retained in the root zone without becoming waterlogged (Araya et al 2022). While variability was too high to show a statistical difference (P ≤ 0.05), the mean saturated hydraulic conductivity of the STNC treatment was roughly three times slower than each of the other treatments (Araya et al 2022).…”
Section: Soil Structure and Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation tillage technology is widely used in agricultural engineering [1][2][3][4]. Notillage, less tillage, and straw mulching are adopted to maintain soil moisture, improve soil structure [5], and slow down land degradation [6][7][8][9][10]. A no-tillage sowing environment for implementing conservation tillage is different from traditional sowing farmland.…”
Section: Introductionmentioning
confidence: 99%